Simulación de un sistema de generación distribuida que permita determinar indicadores de confiabilidad con diferentes escenarios de operación. - Tigselema Gancino, Mayra Leticia (2019)
This research was developed with the objective to determinate how a power system with distributed generation ring interconnected, improves its reliability indices. A simulation in ETAP software which calculate the equivalent reliability of the system was developed in order to verify these indices. Using the Markov calculation method, the system reliability is determined and a study is made in each bar, from each point of generation, and different operating scenarios. The Markov method is used in both cases, the first one making a radial analysis for each scenario using the failure frequency and repair times and in the second one, it uses generations interconnected in parallel and it is calculated directly with the availabilities of each element and using the transformation delta - wye. The data used in the simulator are supposed by the authors and these are approximate to the real ones. Finally, conclusions and recommendations of the analysis are raised.